2022
DOI: 10.1016/j.ijppaw.2021.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Infestation and distribution of chigger mites on Chevrieri's field mouse (Apodemus chevrieri) in Southwest China

Abstract: Based on a long-term field investigation on chigger mites in southwest China from 2001 to 2019, the present study analyzed the infestation and distribution of chigger mites on the Chevrieri's field mouse ( Apodemus chevrieri ) in the region. A total of 12,516 individuals of chigger mites were collected from 1981 A. chevrieri mice, and 12,281 chiggers were identified as 107 species, 11 genera and 3 subfamilies in 2 families, which revealed a high species diversity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 31 publications
4
20
0
Order By: Relevance
“…Previously our research group once reported the species composition and infestation of chiggers on two other rodent species, Apodemus agrarius and A. chevrieri , in Southwest China. The previous reports showed that only 14 chigger species were found on A. agrarius with very low infestation indices ( P m = 3.40%, MA = 0.36, MI = 10.63), and 107 chigger species (higher than on A. agrarius ) were found on A. chevrieri with relatively high infestation indices ( P m = 31.95%, MA = 6.32, MI = 19.77) ( Chen et al, 2021b , 2022 ). The chigger species diversity and infestation indices on E. miletus in the present study were obviously higher than those on A. agrarius and A. chevrieri in the same region ( Chen et al, 2021b , 2022 ).…”
Section: Discussionmentioning
confidence: 95%
See 4 more Smart Citations
“…Previously our research group once reported the species composition and infestation of chiggers on two other rodent species, Apodemus agrarius and A. chevrieri , in Southwest China. The previous reports showed that only 14 chigger species were found on A. agrarius with very low infestation indices ( P m = 3.40%, MA = 0.36, MI = 10.63), and 107 chigger species (higher than on A. agrarius ) were found on A. chevrieri with relatively high infestation indices ( P m = 31.95%, MA = 6.32, MI = 19.77) ( Chen et al, 2021b , 2022 ). The chigger species diversity and infestation indices on E. miletus in the present study were obviously higher than those on A. agrarius and A. chevrieri in the same region ( Chen et al, 2021b , 2022 ).…”
Section: Discussionmentioning
confidence: 95%
“…The previous reports showed that only 14 chigger species were found on A. agrarius with very low infestation indices ( P m = 3.40%, MA = 0.36, MI = 10.63), and 107 chigger species (higher than on A. agrarius ) were found on A. chevrieri with relatively high infestation indices ( P m = 31.95%, MA = 6.32, MI = 19.77) ( Chen et al, 2021b , 2022 ). The chigger species diversity and infestation indices on E. miletus in the present study were obviously higher than those on A. agrarius and A. chevrieri in the same region ( Chen et al, 2021b , 2022 ). The species diversity and infestation of chiggers are often influenced by a series of factors including host species and various environmental factors.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations